History and evolution of improved grain farming systems - Ряба, О. І. (Scientific Progress & Innovations, 2012)
The integral, historical and scientific, impartial and comprehensive analysis of the process and causes of the transition from the fallow and pasture (grass-multi-course) farming systems to the improved grain system has been carried out. The role of centuries-tillage practices, cultural and economic development, the contribution of scientists to the improvement and adoption in farming practice more progressive and adaptive to soil and climatic conditions farming systems has been shown. The attention to historical necessity of the development of the two branches of agricultural production: crop productivity and livestock in transitional farming systems is paid. It has been proved that the creator of the improved grain farming system is V. Levshyn.